Webtelejornalismo universitário: estratégias comunicacionais e discursivas - Thier, Roberta Roos (2019)
The expansion of the web comes leading Journalism transformations which, moreover, has faced new technical paradigms and changes in way of doing it. This reality is also the University Journalism, which before was restricted to the classroom and today can be seen by people all over the world. From this point, the present study has as theme, the interface TV Journalism/University production, with the overall objective to analyze the University news on the web, in regions with or without local television, to understand the configuration strategic assume on the media process. The specific objectives are to verify the insertion of the University journalism on the web, in the context of production in tv journalism in Brazil; understanding the level of belonging of the University web tv journalism, in light of the theoretical choices; the examination of the discursive space occupied by University news displayed and shared via the web; the examination of the constituent elements of the texts provided in the Pampa News and TJ UFSC; and the identification of recurring strategies of these two programs. In this construction, the theoretical methodological path founded on the principles of semiotic theory, developed by Greimas and complemented by his followers, and in methodological proposition developed by Televisual Communication Research Group (COMTV), that refers to three levels of analysis recognized programs: paratextuality, on the surroundings of the empirical object; Intertextuality, concerning the relationship of the program with your model and other texts; and intratextuality, for the relationship at the level of content and expression. As for the results, it was possible to establish relationships between the two programmes examined, recognize their discursive devices and compare their strategies. These regularities allow for the configuration of the grammar of these productions and the definition and conceptual review of this type of production, more specifically identified in the level called webtelejournalism.